Local Original Revenue, General Allocation Fund and Number of Population to District/City Capital Expenditure in North Sumatra Province - Permata Selly Pasa Hartiah; Junita Putri Rajana Harahap (Yayasan Riset dan Pengembangan Intelektual, 2023)
In the District/City Budget in North Sumatra Province, the allocation of Capital Expenditure is still relatively small when compared to other regional expenditures. The contribution of Regional Original Revenue to Regional Revenue is still not optimal. Where regional revenues are still dominant in the General Allocation Fund. This explains that Regional Original Revenue has not been able to finance its Capital Expenditure. Capital Expenditure is budgeted for public services in the form of facilities and infrastructure where the Number of Population in Districts / Municipalities in North Sumatra Province continues to increase while Capital Expenditure fluctuates. This study aims to determine the effect of Regional Original Revenue, General Allocation Fund and Number of Population on District / City Capital Expenditure in North Sumatra Province. This study uses secondary data obtained from the Directorate General of Financial Balance and the Central Statistics Agency in 2020-2021. The population in this study is 33 regencies/cities in North Sumatra Province during 2020-2021. The sampling technique used is saturated sampling. The data analysis method uses Descriptive Statistics, Normality Test, Multiple Linear Regression and Hypothesis Test. The results showed that partially Regional Original Revenue affects Capital Expenditure, General Allocation Fund affects Capital Expenditure, and Number of Population affects Capital Expenditure. The results of test f simultaneously show that Regional Original Revenue, General Allocation Fund and Number of Population together affect District / City Capital Expenditure in North Sumatra Province.